MODEL BIMBINGAN KONSELING KOMPREHENSIF DALAM MEMBERIKAN LAYANAN PRANIKAH BAGI MAHASISWA - Fatmawati Fatmawati; Nurhastuti Nurhastuti (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2021)
Premarital education for students is considered necessary because, at this time, a person must be prepared to enter married life. Premarital education is one of the preparations that can be done by early adults in marriage and has a goal in preventing divorce. This study aims to formulate a hypothetical comprehensive guidance and counselling program to improve students' self-readiness in facing marriage and family life. This type of research is development research or Research and Development methods, namely research strategies used to produce specific products. This research will be conducted at Padang State University, namely to students of Special Education, Faculty of Education. The results of this study are (1) In general, special education department’s students of the Faculty of Education, Padang State University, as early adults, have less interest in preparing for their marriage. (2) The comprehensive premarital guidance and counselling model for students developed in this study is formulated from a theoretical framework based on field findings, consisting of 7 rational components, key concepts, vision & mission, model objectives, the content of guidance and counselling, control, and organization & personnel. (3) Based on the model validation test conducted by three counsellors on the General Guidelines for the Development of Comprehensive Premarital Guidance and Models for Students, it shows that the contents of the general guidelines are categorized as suitable or adequate.